Carbon-based biomass-derived catalysts for deoxygenation of fast pyrolysis bio-oil - Recio-Ruiz, María del Carmen; García-Mateos, Francisco José; Ruiz-Rosas, Ramiro Rafael; Rosas-Martínez, Juana María; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (My University, 2023)
Producing energy and chemicals from biomass is an interesting alternative for replacing conventional fossil sources with a renewable feedstock while enabling zero net greenhouse gases emissions. Particularly, fast pyrolysis of biomass waste enables the production of bio-oil, which can be upgraded to biofuels or value-added chemicals. The sustainability of this process can be enhanced by preparing carbon-based catalysts from the same biomass waste used as raw material for the biooil production, decreasing the inputs of the process and allowing recovery and recycle of the active phase by combustion of the carbon substrate. In this work, catalytic fast pyrolysis of olive stone residues was studied using mesoporous carbon-based acid catalysts prepared by activation with H3PO4 of olive stones.
Keywords: Energía de biomasa; Fast Pyrolysis; Bio-oil; Biomass